Paradigm Shift to Forensic Engineers for Addressing Structural Failures in India (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Urban sprawl and high-rise buildings are essential for meeting housing demands and optimising land use, thereby mitigating urban sprawl through vertical urbanisation in densely populated cities. This paper explores the evolution of forensic structural engineering through various case studies, emphasising the urgent need for forensic engineers and their recommendations following structural failures, including subsequent legal actions. Case studies of structural collapses in Bengaluru and Gurgaon are examined. In these instances, buildings were illegally constructed, resulting in fatalities. Forensic engineers, acting as consultants, discuss issues such as weak foundations, poor construction quality, and unauthorised vertical extensions, which violate building codes and bylaws. These violations have led to a disregard for quality and safety standards.The study employs Normalised Differential Built-up indices using Geographic Information Systems (GIS) to assess the increase in the built-up index. This article reviews the utility matrix of forensic engineers and highlights their growing importance in recent years. Furthermore, the discussion underscores the significance of geotechnical engineering, the need for stringent building codes that focus on people, materials, and machinery, regular inspections, and effective disaster management. The analysis draws lessons for policymakers, builders, and the community aimed at preventing illegal construction practices and enhancing disaster management strategies, thereby reducing the risk of structural failures.